2020
DOI: 10.31234/osf.io/2f7cg
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effects of Shinrin-Yoku Retreat on Mental Health: A Pilot Study in Fukushima, Japan

Abstract: Shinrin-yoku (forest bathing) is a cost-effective healing practice, and has attracted the interest of scientists. Recently, its effects on mental health has been increasingly reported. Japanese university students suffer from high rates of mental health problems, and the number of suicides remain high, despite the total number of suicides in Japan has been decreasing. Effective mental health approaches are sought after for Japanese students, however healthful treatment has not been identified to date. Accordin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Furuyashi [ 57 ] conducted a more extensive study with 155 participants classified into two groups: those with and without depressive tendencies. Shinrin-yoku therapy’s length also varied: three-day retreat [ 64 ], six times a day for 15 min [ 55 ]. Before and after forest therapies, reduced items related to psychopathology, irritability, restlessness, emotional instability, egocentrism, relativity, and negativism were evaluated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furuyashi [ 57 ] conducted a more extensive study with 155 participants classified into two groups: those with and without depressive tendencies. Shinrin-yoku therapy’s length also varied: three-day retreat [ 64 ], six times a day for 15 min [ 55 ]. Before and after forest therapies, reduced items related to psychopathology, irritability, restlessness, emotional instability, egocentrism, relativity, and negativism were evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…It is a therapeutic method that can be used to prevent the treatment and rehabilitation of stress disorders and civilisation diseases and help treat mental disorders such as anxiety-depressive disorders [ 53 ]. Kotera and Fido [ 63 , 64 ] demonstrated that the mean scores for mental well-being, self-compassion, common humanity, and mindfulness had increased significantly from pre-retreat to post-retreat.…”
Section: Methodsmentioning
confidence: 99%
“…In these studies, the authors reported a wide range of research methodologies to examine the effect of forest on mental health including the number of visits to the forest which ranged from just a single session [19,25,29 ▪▪ ] to multiple sessions over several few weeks [23 ▪ ,24 ▪▪ ,26,28 ▪ ,30]. The duration for each visit also varies ranging from 10 [31 ▪ ] to 15 min [18 ▪ ,32 ▪ ] or up to 300 min [28 ▪ ,33].…”
Section: Therapeutic Forestmentioning
confidence: 99%